The Earth: An Alien Planet in another Universe (Global Journal of Science Frontier Research, 2022)
The true future perspective of the Earth can be understood and appreciated only if there is a true reconciliation with its past. There are several competing theories about the ultimate fate of the universe and possibility of anything preceding the Big Bang, while other physicists and philosophers refuse to speculate, doubting that information about prior states will ever be accessible. Some scientist have suggested various multiverse hypotheses, in which our universe might be one among many universes that likewise exist. There has been so many possibilities that are yet to be explored and investigated about our earth. The Earth is strangely different from other member of the universe. This study and observation intended to interpret the likelihood of our Earth been a stranger in a foreign universe.
Keywords: universe; earth; planets; stars; galaxy